PELAKSANAAN PROGRAM PENGAWASAN PARTISIPATIF BADAN PENGAWAS PEMILU (BAWASLU) KOTA PEKANBARU TAHUN 2024 - Afilla, Riska Diva; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Law Number 7 of 2017 Article 1 Paragraph 17 regulates that "the Election Supervisory Body (Bawaslu) as an election organizing institution throughout Indonesia" has the authority to, among other things, supervise the implementation of election stages, receive reports of alleged election/regional election violations, and follow up on findings or reports to authorized agencies. Supervision carried out by independent institutions and community supervision to realize the main objectives of the election itself. This is known as participatory supervision. Participatory supervision is contained in Bawaslu Regulation No. 2 of 2023. This study aims to determine how the implementation of the participatory supervision program of the Pekanbaru City Bawaslu in 2024 and the obstacles faced. This study is a study that uses a qualitative method presented descriptively based on secondary and primary data using data collection techniques through interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. This study is based on the participatory supervision theory put forward by Suswantoro. The indicators of participatory supervision consist of limited, broad and issue-based participatory supervision models. The results of this study indicate that in the implementation of the participatory supervision program, Bawaslu Pekanbaru City has a superior program, namely the participatory supervision socialization program. There are three types of participatory supervision discussed, namely limited, widespread and based participatory supervision. Each indicator has its own strategy to improve the participatory supervision socialization program. However, in the implementation there are obstacles such as factors from the community, budget limitations and human resource limitations Keywords: Bawaslu, Participatory Supervision, Program